Dectin-1 expression by macrophages and related antifungal mechanisms in a murine model of Sporothrix schenckii sensu stricto systemic infection - Jellmayer, Juliana Aparecida [UNESP] (2017)
The available information about the role of Dectin-1 in sporotrichosis is scarce. Hence, we aimed to assess Dectin-1 expression by macrophages and the activation of some related antifungal mechanisms during the Sporothrix schenckii sensu stricto infection as a first attempt to elucidate the role of this receptor in sporotrichosis. Balb/c mice were intraperitoneally infected with S. schenckii sensu stricto yeast ATCC 16345 and euthanized on days 5, 10 and 15 post-infection, when the following parameters were evaluated: fungal burden in spleen, Dectin-1 expression and nitric oxide (NO) production by peritoneal macrophages, as well as IL-1β, TNF-α and IL-10 ex vivo secretion by these same cells. Peritoneal macrophages were ex vivo challenged with either the alkali-insoluble fraction (F1) extracted from the S. schenckii cell wall, a commercially available purified β-1,3-glucan or whole heat-killed S. schenckii yeasts (HKss). Additionally, a Dectin-1 antibody-mediated blockade assay was performed on day 10 post-infection to assess the participation of this receptor in cytokine secretion. Our results showed that Dectin-1 expression by peritoneal macrophages was augmented on days 10 and 15 post-infection alongside elevated NO production and ex vivo secretion of IL-10, TNF-α and IL-1β. The antibody-mediated blockade of Dectin-1 inhibited cytokine production in both infected and non-infected mice, mainly after β-1,3-glucan stimulation. Our results suggest a role for Dectin-1 in triggering the immune response during S. schenckii infection.